Relasi Kuasa dalam Novel Anjing Mengeong, Kucing Menggonggong Karya Eka Kurniawan: Perspektif Michael Foucault - Lulyastuti, Lulyastuti; Satriani, Irma (Fakultas Sastra Universitas Muslim Indonesia, 2025)
This journal discusses the analysis of power relations in the novel Anjing Mengeong, Kucing Menggonggong by Eka Kurniawan using Michael Foucault's perspective. The research method used in this analysis is the qualitative description method. This method is a research process that produces descriptive data in the form of words rather than numbers. In the analysis of the novel Anjing Mengeong, Kucing Menggonggong by Eka Kurniawan, a descriptive method was used. This research uses analytical techniques which aim to find the data contained in the novel to make data collection and classification easier. The results of the analysis of the novel Dog Meowing, Cats Menggonggong by Eka Kurniawan in this analysis can be found several evidences of relationships that exist in this literary work. In the novel, it is described how the father's power is reflected not only in harsh actions, but also in the form of words spoken to control the child's body. Apart from that, it was also found that there were authorities who were able to cause feelings of humiliation in the child. In Foucault's perspective, power can also appear as a form of control that is internalized by individuals.